PENGARUH KECEPATAN PENGELASAN MIG TERHADAP KEKUATAN TARIK DAN PERUBAHAN STRUKTUR PATAHAN MAKRO PADA SAMBUNGAN ALUMINIUM - Kris Witono; Talifatim Machfuroh; Lisa Agustriyana; Siti Duratun Nasiqiati Rosady (Universitas Negeri Surabaya, 2025)
MIG (Metal Inert Gas) welding is a welding process that uses rolled electrodes which are the same as the base metal and uses a protective gas. Aluminum is one of the most commonly used metals in the industrial world. Connecting aluminum by welding is a challenge in itself because of its high heat conductivity. This is why a lot of research has been carried out on welding aluminum. This research aims to investigate the effect of travel speed on the tensile strength and macro structure of welds from the robotic welding process. The research was carried out using experimental methods and observing the macro structure of the fracture results. The research results, it was found that changes in welding speed (travel speed) in the aluminum MIG welding process showed a decreasing trend in maximum tensile strength. The highest tensile strength was obtained at the TS variation of 40 mm/minute, while at TS 70 mm/minute the tensile strength was lower. The higher the welding speed, the lower the resulting tensile strength. This is due to reduced heat applied which affects weld penetration and metal joining. A lower welding speed results in better penetration and higher tensile strength, but a speed that is too slow can cause overheating and damage the metal micro structure. The macro structure of the fracture, it was found that higher welding speeds cause fractures that tend to be brittle with defects such as porosity, which can also reduce tensile strength